Preparation of Bromodeoxycellulose and Derivatives from Shambat Cotton Lint Using Dimethyl Acetamide / Lithium Bromide Solvent System - A. M. Salim, Inaam; A. Ragab, Yousif (Gezira Journal of Engineering and Applied Sciences; Vol 8 No 2 (2013), 2013)
This study was designed to prepare cellulose derivatives  with different   functional  groups  from  Sudanese  Shambat  cotton lint using   a homogenous   solubilisation  medium. The raw cotton lint was   mercerized    in   (15%)   NaOH     solution   to   weaken   the aggregation   of    the   bundles   of   cellulose    fibers;    and    was subsequently      dissolved      in     N,N-dimethylacetamide/lithium bromide    (DMA/LiBr)    as    a homogenous      solvent     system. Bromodeoxycellulose   was    synthesized   by   treatment,   of   the     solubilised   cotton  cellulose with N-bromosuccinimide (NBS)  in the    presence   of   triphenylphosphine   (Ph 3 P)   to   convert   the hydroxyl  groups  into  the  bromodeoxy  derivative  of   cellulose. The  chemical   structure  this  derivative  was  investigated  using infrared  spectroscopy,  elemental  analysis  which  confirmed  the presence  of  C-Br   bonds.  Thermal   analysis   (TGA,  DSC)  has shown     that    unlike   chlorordeoxycellulose    and    unmodified mercerized  cotton, bromodeoxycellulose was relatively thermally stable.  Azido  and  amino  deoxycellulose  were   easily  prepared from   bromodeoxycellulose   since   bromide   is  a good  leaving. Solubility in some organic solvents was tested to explore possible new uses and applications.